A Study on Biocompatibility of Three Endodontic Sealers: Intensity and Duration of Tissue Irritation - Moura, Camilla Christian Gomes; Cunha, Thais Cristina; Crema, VirgÃnia Oliveira; Dechichi, Paula; Biffi, JoÃ£o Carlos Gabrielli (Iranian Endodontic Journal, 2014)
Introduction: Several studies have evaluated the inflammatory reaction triggered by Epiphany (EPH), a contemporary endodontic sealer. However, they used conventional parameters, which need additional analysis to better understand the reactions induced by this sealer compared to other traditional sealers. Methods and Materials: The intensity and time span of tissue irritations for three endodontic sealers were assessed by inflammatory reactions, fibrous capsule measurement and mast cell counts. Tubes containing freshly mixed EPH, AH plus (AHP) and Endofill (ENF) were subcutaneously implanted into the backs of 28 Wistar rats. The side wall of the tube was used as the control. At 14, 21, 42 and 60 days, the connective tissue surrounding the implants (n=7) was stainedfor histopathological analysis. The Friedman test was applied to compare the results. The level of significance was set at 0.05. Results: At days 14 and 21, a significant difference among the groups was observed, with the ENF showing the worst tissue response (P<0.001). ENF remained the most aggressive sealer at 42 and 60 days, compared with EPH (P<0.05). No differences were found for the fibrous capsule thicknesses among the groups in each period. The number of mast cells per field did not show difference among the sealers at 21 and 60 days. Conclusions: EPH and AHP elicited similar patterns of irritation, as demonstrated by the inflammatory scores and fibrous capsule thicknesses. ENF caused the highest degree of tissue damage. The increase in mast cell counts observed during the early and late periods shows the possibility of late hypersensitivity to the test materials.